BOShLANG‘ICh SINFLARDA OʻQUVChILARNING OʻQISh SAVODXONLIGINI BADIIY-ESTETIK TAHLIL VOSITASIDA RIVOJLANTIRISh TEXNOLOGIYASI - Uteniyazov, Z.B. (SCIENCE and SOCIETY, 2025)
The article discusses artistic and aesthetic analysis technologies for improving reading literacy in primary school students, fostering interest in reading, developing reading techniques, improving speech, methods of text analysis, and ways to improve reading speed and comprehension.
Keywords: reading literacy; primary school; artistic and aesthetic analysis; reading technique; speech development; methodological approach; fast reading